Communication Style in Indonesia’s Television Series: My Nerd Girl - Duha, Ekrisyen; Umar Mono; Alemina Perangin Angin (Austronesian: Journal of Language Science & Literature, 2022)
This research is about communication styles in Indonesia’s television series. The research was conducted because it had an interesting and unique phenomenon in it where the characters or actors and actresses had a certain communication style, which makes it interesting to be conducted. The communication style and the way of actors in Indonesia’s Television series ‘My nerd girl’ communicate are the aims of this research. This research was descriptive qualitative research because it aimed to describe and explain in depth a case that would be researched. The data was documentation which consists of the video and transcript of Indonesia’s television series called My Nerd Girl. The data was analyzed by using theory of Miles, Huberman and Saldana, which consists of three steps: data reduction, data display, and conclusion drawing/verification. The research results showed that the communication style found in Indonesia’s Television series ‘My nerd girl’ are into slang, bad words, positive, and negative words. Another research result revealed that the way of communication in that series is just a style of speaking or the style of communication, which means certain characters speak English naturally in some scenes.